Analysis of אמצים [’mṣîm] in the Hexapla - Philip Chia (Collectanea Theologica, 2025)
The term אמצים as encountered in Zech 6:3 and 6:7 has been interpreted in various ways by ancient translators, including the LXX, Peshitta, Targum, Vulgate, and the Masoretic Text. The ambiguity surrounding אמצים is further highlighted in Origen’s Hexapla. Importantly, there is no agreement on the translation of אמצים in Zech 6:7. Aquila’s translation is particularly significant, as it offers a unique interpretation of אמצים in Zech 6:3 that differs from his rendering in Zech 6:7. This article argues that Aquila’s version of Zech 6:7 does not correspond to the Hebrew text that underlies the Masoretic Text, whereas both Symmachus and Theodotion are consistent with the Hebrew reading of the Masoretic Text. Textual criticism is utilized to support this claim.